TRANSFER PENGETAHUAN SOFTSKILL KUNDENBERATER - Soumokil, Piet; Maruanaya, Rita Fransina; Karuna, Kalvin (Universitas Pattimura, 2025)
This Community Service (PkM) activity aims to transfer knowledge related to essential soft skills required in the profession of Kundenberater (customer consultant) to students of the German Language Education Study Program. The initiative is driven by the growing need to equip students not only with academic knowledge but also with non-technical competencies that support their readiness for the workforce, particularly in intercultural communication and customer service. The methods applied include interactive dialogue, group discussions, and Q&A sessions, which encourage active participation and critical reflection among the participants. Through this approach, students gain not only theoretical insights but also the ability to connect this knowledge to real-life situations they may encounter in the field. The outcomes of the activity show an increased understanding of the roles and responsibilities of a Kundenberater, along with the communication skills required in such a role. Moreover, the activity enhances students’ confidence in engaging in professional interactions. The conclusion of this program emphasizes that knowledge transfer through dialogue and discussion is effective in fostering awareness and foundational soft skills relevant to the job market, particularly within the context of German language education.